1991
DOI: 10.1126/science.2000493
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Cranial and Cervical Innervation of Wing Muscles: New Evidence for Bat Monophyly

Abstract: The traditional view that Old World fruit bats (Megachiroptera) and insect bats (Microchiroptera) are closely related has been challenged by claims that Megachiroptera are the sister group to flying lemurs (Dermoptera) or Primates. We found that the specialized muscles of the rostral part of the wing in Microchiroptera and Megachiroptera receive double innervation by both the facial nerve and cervical spinal nerves, suggesting that bats are monophyletic. Innervation by the facial nerve also occurs in Dermopter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 9 publications
2
37
0
Order By: Relevance
“…This indicates the occipito-pollicalis associated with bat wings is derived from cranial paraxial mesoderm that later migrates into the second pharyngeal arch of the embryo. This is mostly consistent with results based on the dissection of adult bats 15 . The coraco-cutaneus and humeropatagialis within the plagiopatagium were innervated by spinal nerves that constitute the brachial plexus: cervical nerves 5-8 (C5-C8) and thoracic nerve 1 (T1) (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This indicates the occipito-pollicalis associated with bat wings is derived from cranial paraxial mesoderm that later migrates into the second pharyngeal arch of the embryo. This is mostly consistent with results based on the dissection of adult bats 15 . The coraco-cutaneus and humeropatagialis within the plagiopatagium were innervated by spinal nerves that constitute the brachial plexus: cervical nerves 5-8 (C5-C8) and thoracic nerve 1 (T1) (Fig.…”
Section: Resultssupporting
confidence: 91%
“…To identify the developmental origin and the homology of these muscles, we examined the innervation pattern, which has been used as a criterion for establishing muscle homology because of its close link to myogenesis 15 . Our analysis revealed that both proximal and distal elements of the occipito-pollicalis were solely innervated by cranial nerve VII (the facial nerve), as well as the auricularis and the platysma (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…hypothesis is based on the analysis of neural connections between the retina and midbrain, but it is inconsistent with the conclusion of molecular [10,15,18] and morphological studies [1,9,19].…”
mentioning
confidence: 93%